Incidence of Helicobacter Pylori in Patients with Nonnuclear Dyspepsia (Medical Forum Monthly, 2024)
Objectives: To perform a systematic review of the literature to determine whether chronic infection with H. Pylori is relevant to nonnuclear or uninvestigated dyspepsia. Study Design: Hospital base prospective study Place and Duration: The study was carried in Department of Medicine Sandeman Provincial Hospital Quetta from January 2010 to January 2011. Background: Previous studies have yielded conflicting results and substantial uncertainty about any independent association of Helicobacter pylori infection with dyspepsia. Patients and Methods: 120 patients, 72 Males and 48 females belonging to age group 17 years to 70 years, with upper abdominal symptoms were examined with an Olympus CIF X Q 10 Gastroscope. Patients who had endoscopic features of gastritis and the patients with normal looking gastric mucosa on endoscopy but with upper abdominal symptoms, had biopsies taken from gastric antum and body for histological and microbiological examination. None of these patients treated with antibiotic or Bismuth preparations before this gastoscopic examination. H2 receptor antagonists were discontinued at least one week before the endoscopic examination. Results: In our study 120 cases with upper abdominal symptoms were entered. They were between 17-70 years of age.72 were Male and 48 were female.82 patients who had histological evidence of gastritis had positive H.pylori infestation of gastric mucosa.38 cases were with normal histological findings were negative for H.pylori infestation. Association of H.pylori and endoscopic evidence of gastritis was 60%.68% of patient who had histological evidence of gastritis had positive H.Pylori infestation and 32% cases with normal histological findings or negative for H.Pylori. Conclusion: The role of H.pylori in the pathogenesis of chronic gastritis and peptic ulceration has thrown new light of etiology of this condition, but our study revealed the role of H.Pylori in NUD. In the view of above mention study the prevalence of H.pylori with NUD was 68%.Patient with histological proven were 100% positive for H.Pylori infestations in gastric mucosa. In the end question arises whether to treat such patient with H.Pylori eradication therapy to prevent the high rate of the recurrence of symptoms and gastritis in these patient whether these therapy will be cost effective and beneficial for the patient remains to be discovered and open the new door for research.